Understanding the enlargement of the Eurasian Economic Union: The case of Armenia and Kyrgyzstan - Syssoyeva, Rigina (Politikon: The IAPSS Journal of Political Science, 2019)
The research note addresses the enlargement of the Eurasian Economic Union (EAEU), which Armenia and Kyrgyzstan joined shortly after its establishment in 2015. In theoretical terms, it aims to test Frank Schimmelfennig’s concepts on enlargement of integration communities. In practical terms, it seeks to answer why and how new members enter the EAEU. Qualitative research methods, such as historical, deductive and comparative analysis, to demonstrate that Schimmelfennig’s theoretical concepts can explain the process of enlargement of the EAEU.